Against barbarism and lack of communication by building a learning society - Brandalise, Roberta; Assencio, Sandro (MATRIZes, 2014)
A comunicação na educação, written by Jesús Martín-Barbero, deals with issues concerning the process of literacy in communication in its many interfaces with culture; the decentralization of the school as the primary socializing agency and questions the hegemony of literacy culture to enhance orality and visibility as forms of knowledge construction; proposes a shift from educational system to a society of shared knowledge translated into an educational city project.